2010
DOI: 10.1080/01638530903416257
|View full text |Cite
|
Sign up to set email alerts
|

Using Diagnostic Text Information to Constrain Situation Models

Abstract: During reading, the model of the situation described by the text is continuously accommodated to new text input. The hypothesis was tested that readers are particularly sensitive to diagnostic text information that can be used to constrain their existing situation model. In 3 experiments, adult participants read narratives about social situations that were ambiguous in terms of whether they involved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, although Dutke and von Hecker's (2011) study focused on the structure of social relations described in the text to investigate inferential revision, they did not use moment-bymoment processing measures to study revision during the construction of the situation model. Moreover, in a separate study, Dutke and colleagues found evidence indicating that some of the situation model revision took place after reading the text (Dutke, Baadte, Hähnel, von Hecker, & Rinck, 2010), which leaves open the question of whether the revision process may occur when reading the text (that is online) under certain circumstances.From our point of view, it is important to understand the time course and accuracy with which readers revise inferential information in their situation model, to elucidate reading comprehension problems at a high level of processing. Thus, the present study aims to investigate the inferential revision process in two important ways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, although Dutke and von Hecker's (2011) study focused on the structure of social relations described in the text to investigate inferential revision, they did not use moment-bymoment processing measures to study revision during the construction of the situation model. Moreover, in a separate study, Dutke and colleagues found evidence indicating that some of the situation model revision took place after reading the text (Dutke, Baadte, Hähnel, von Hecker, & Rinck, 2010), which leaves open the question of whether the revision process may occur when reading the text (that is online) under certain circumstances.From our point of view, it is important to understand the time course and accuracy with which readers revise inferential information in their situation model, to elucidate reading comprehension problems at a high level of processing. Thus, the present study aims to investigate the inferential revision process in two important ways.…”
mentioning
confidence: 99%
“…However, although Dutke and von Hecker's (2011) study focused on the structure of social relations described in the text to investigate inferential revision, they did not use moment-bymoment processing measures to study revision during the construction of the situation model. Moreover, in a separate study, Dutke and colleagues found evidence indicating that some of the situation model revision took place after reading the text (Dutke, Baadte, Hähnel, von Hecker, & Rinck, 2010), which leaves open the question of whether the revision process may occur when reading the text (that is online) under certain circumstances.…”
mentioning
confidence: 99%